2015
DOI: 10.1111/dote.12368
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for eosinophilic esophagitis in children with esophageal atresia

Abstract: Eosinophilic esophagitis (EoE) has been reported to be more prevalent in patients with esophageal atresia/tracheoesophageal fistula (EA-TEF). To date, there is limited data on the management of EoE in this group of patients. The aim of this study is to evaluate the treatment outcomes of EoE in children with EA-TEF. A retrospective chart review was performed on all EA-TEF children who were diagnosed with and treated for EoE between January 2000 and September 2013 at the Sydney Children's Hospital. Data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 27 publications
4
32
1
2
Order By: Relevance
“…A high proportion of these patients exhibit evidence of food and/aeroallergen sensitisation and peripheral eosinophilia [102][103][104]. Chronic dysphagia that persists after oesophageal dilation and despite having achieved a normal calibre for the oesophageal lumen was found to be common among these patients [103], who also presented endoscopic features characteristic of EoE [102].…”
Section: Oesophageal Atresia and Eosinophilic Oesophagitismentioning
confidence: 99%
See 1 more Smart Citation
“…A high proportion of these patients exhibit evidence of food and/aeroallergen sensitisation and peripheral eosinophilia [102][103][104]. Chronic dysphagia that persists after oesophageal dilation and despite having achieved a normal calibre for the oesophageal lumen was found to be common among these patients [103], who also presented endoscopic features characteristic of EoE [102].…”
Section: Oesophageal Atresia and Eosinophilic Oesophagitismentioning
confidence: 99%
“…Several case reports and short case series published in the last decade have suggested that EoE is a frequent concomitant problem in patients with a history of congenital oesophageal deformities, specifically oesophageal atresia [100][101][102][103][104]. Oesophageal atresia, with or without an associated tracheo-oesophageal fistula, is a relatively common congenital malformation, with a live-birth prevalence of 1.8 per 10,000 births [105].…”
Section: Oesophageal Atresia and Eosinophilic Oesophagitismentioning
confidence: 99%
“…Results demonstrated that treatment improved dysphagia and reflux symptoms, and reduced eosinophil count, strictures, and the number of dilations required. 25 For the management of EoE and EA, the ESPGHAN and the NASPGHAN recommend to consider the consensus established for EoE treatment in the general population. 1,19 In sum, several authors consider it is important to study dysphagia, recurrent strictures, difficulty eating, and PPI-refractory reflux symptoms in patients with EA, not only with a contrast study but also with an EGD and multiple biopsies before performing an esophageal dilation and anti-reflux surgery.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 99%
“…Los resultados demostraron que el tratamiento mejoraba los síntomas de disfagia y reflujo, disminuía el recuento de eosinófilos, estenosis y el número de dilataciones requeridas. 25 Para el manejo de EEo en AE, la ESPGHAN y NASPGHAN recomiendan tener en cuenta el consenso para tratamiento de EEo en la población general. 1,19 En resumen, diversos autores consideran importante investigar la disfagia, las estenosis recurrentes, las dificultades en la alimentación y los síntomas de reflujo refractarios a IBP en pacientes con AE, no solo con estudio contrastado, sino también con VEDA y múltiples biopsias antes de realizar una dilatación esofágica y cirugía antirreflujo.…”
Section: Atresia De Esófago Y Esofagitis Eosinofílicaunclassified
“…La dilatación endoscópica se reserva para estenosis refractarias a pesar del tratamiento adecuado de su EEo y/o ERGE o si clínicamente está indicada (Figura 6). 6,18,19,25 n…”
Section: Atresia De Esófago Y Esofagitis Eosinofílicaunclassified